Maternal and perinatal outcome related to severity of chronic hypertension in pregnancy - Muhammad Ilham Aldika Akbar, - (Elsevier BV, 2019)
Objectives Chronic hypertension in pregnancy is an important cause of maternal and neonatal morbidity and mortality. The aim of this study was to determine the effect of severity of chronic hypertension in pregnancy on maternal and perinatal outcome in an Indonesian population. Study design This study was performed in Dr Soetomo General Hospital, a tertiary center in East – Java, Indonesia over the period of 2013–2017. Chronic hypertension (CH) was divided using JNC VII criteria, as stage 1 (Blood pressure ≥140/90 mmHg) and Stage 2 (BP > 160/110 mmHg) hypertension. Main outcome measures The primary outcomes were maternal and perinatal outcome. Data was statistically analyzed using Chi-square, Fischer exact test, and Mann-Whitney test (program: SPSS ®23). Results Over these 5 years, 352 patients were diagnosed with CH. The stage 2 of CH was associated with worse maternal outcome: maternal death (5.6% vs 0.8%; p = 0.016), laboratory values of urinary protein +3 (67% vs 21,5%, p = 0.001) and +4 (12.3% vs 0.4%, p = 0.001), LDH > 600 IU/L (11.3% vs 5.3%, p = 0.04), ALT > 70 IU/L (11.3% vs 4.1%, p = 0.01), AST > 70 IU/L (12.3% vs 5.3%, p = 0.02), BUN > 25 mg/dL (27.4% vs 8.1%, p = 0.001), SK > 1.1 mg/dL (29.2% vs 6.5%, p = 0.001) and Albumin <3 g/dL (65.1% vs 10.2%, p = 0.001), need for ICU admission (76.4% vs 36.6%, p = 0.001), mechanical ventilation (48.1% vs 21.1%, p = 0.001), and occurrence of complications (72.6% vs 57.7%, p = 0.006). Stage 2 CH in pregnancy was associated with an increased risk of maternal death (OR: 7.22; 95% CI: 1.43–36.36; p = 0,016). Stage 2 CH was also associated with worse perinatal outcome, in terms of lower birth weight (1635 ± 863.27 vs 2063.74 ± 935.43, p = 0.001), lower Apgar score (p = 0.001), and number of intra uterine complications such as: IUGR, stillbirth, and placental abruption (27.4% vs 11.8%, p = 0.001). Conclusions Stage 2 CH in pregnancy is associated with worse maternal and perinatal outcomes compared with stage 1. Intervention to prevent disease progression to stage 2 before pregnancy may improve maternal and perinatal outcomes during pregnancy.